2009
DOI: 10.1088/0031-9155/54/6/r01
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound contrast microbubbles in imaging and therapy: physical principles and engineering

Abstract: Microbubble contrast agents and the associated imaging systems have developed over the past twenty-five years, originating with manually-agitated fluids introduced for intra-coronary injection. Over this period, stabilizing shells and low diffusivity gas materials have been incorporated in microbubbles, extending stability in vitro and in vivo. Simultaneously, the interaction of these small gas bubbles with ultrasonic waves has been extensively studied, resulting in models for oscillation and increasingly soph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
248
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(258 citation statements)
references
References 245 publications
2
248
0
Order By: Relevance
“…Their use as echo contrast agents for improved sonography (e.g., echocardiography) has become standard. 83 Protein microspheres have also been developed as 19 F-MRI contrast agents, 84 as in vivo MRI temperature probes, 85 as optical coherence tomography contrast agents, 86 for encapsulation and drug release, [87][88][89] and as multifunctional, multimodal cancer imaging contrast agents. 90 The combination of chemical and physical effects of ultrasound can also be applied to prepare organic latex beads in a one-pot fashion.…”
Section: Combined Chemical and Physical Effects For Ultrasonic Synthementioning
confidence: 99%
“…Their use as echo contrast agents for improved sonography (e.g., echocardiography) has become standard. 83 Protein microspheres have also been developed as 19 F-MRI contrast agents, 84 as in vivo MRI temperature probes, 85 as optical coherence tomography contrast agents, 86 for encapsulation and drug release, [87][88][89] and as multifunctional, multimodal cancer imaging contrast agents. 90 The combination of chemical and physical effects of ultrasound can also be applied to prepare organic latex beads in a one-pot fashion.…”
Section: Combined Chemical and Physical Effects For Ultrasonic Synthementioning
confidence: 99%
“…Since then, microbubbles are widely used as Ultrasound Contrast Agents (UCA) in medical imaging, [2][3][4][5][6][7][8] owing to their capability of enhancing the reflection of ultrasound (US) waves. 9,10 Besides their use as contrast agents in diagnostics purposes, these microbubbles in conjunction with ultrasound have been off late used as a tool for targeted drug delivery and gene therapy. [11][12][13][14][15][16] UCA or ultrasound contrast microbubbles are small (typically 1-8 lm in diameter) gasfilled microspheres and are coated with an adsorbed layer of proteins, 17 polymers, 18 or lipids.…”
Section: Introductionmentioning
confidence: 99%
“…These properties allow for highly specific time-resolved imaging of tumor vasculature a) Electronic mail: akummel@ucsd.edu and perfusion. [9][10][11][12] Since cancers exhibit accelerated metabolism, they promote the development of new blood vessels; different types of cancers will often possess characteristic patterns to their vasculature which allow identification of the tumor type with CEUS. [13][14][15] Previous reports have shown that analysis of timeintensity curves (TICs) can produce hemodynamic measurements such as the area under the curve (AUC) and time to peak (TTP) that have statistical significance between benign and malignant lesions of various types of tumors.…”
Section: Introductionmentioning
confidence: 99%